Comparing the Effect of Standardized Patient-Based Training with Team-Based Learning on the Midwifery Students` Skill in Taking History of Rape Victims - Zahra Norouzi; Farzaneh Jafarnezhad; Talat Khadivzadeh; Arya Hedjazi; Habibollah Esmaily (Mashhad University of Medical Sciences, 2019)
Background & aim: Accurate history-taking from sexual assault victims is the basis of correct diagnosis and treatment. Considering the serious consequences of sexual assault and the necessity of students' training through active educational methods, this study was conducted to compare the effect of standardized patient-based training and team-based learning on the midwifery student' skill of history-taking from the victims of sexual assault. Methods: This quasi-experimental study was conducted among 75 students of nursing and midwifery in Mashhad University of Medical Sciences, Mashhad, Iran. The subjects were randomly assigned to two groups of standardized patient-based training (38 students) and team-based learning (37 students). After holding a pre-test, each group trained separately for 2 hours. Post-test was held a week post-intervention. Data were collected using a questionnaire containing demographic data, educational profiles, and performance checklist. Data analysis was performed in SPSS software, version 4. Results: The groups were equal regarding demographic, educational, and occupational data. The average score of students' history-taking skill at the post-intervention phase was 32.0±2.3 and 30.0±4.5 in the standardized patient-based training and team-based learning groups, respectively (P=0.015). There was a significant difference between the groups considering the increase of scores (P=0.039). Conclusion: The impact of using a standardized patient-based training approach on improving the skill of student in history-taking of sexual assault victims was more than team-based learning.